Vocational Stereotyping of People Who Stutter: Human Resource Management Students. - Abou-Dahech, Tala; Gabel, Rodney (Perspectives of the ASHA Special Interest Groups, 2020)
Purpose: The purpose of this study was to investigate whether human resource management (HR) students report negative vocational stereotypes of people who stutter (PWS). Though past research has explored how a variety of population groups perceived career choices for PWS, no studies have explored the perceptions that HR students hold regarding career options for PWS. Method: An online questionnaire using the Vocational Advice Scale) was completed by 220 students pursuing a degree in HR or related fields at the University of Toledo. The Vocational Advice Scale has been used often to explore career advice and vocational stereotyping of PWS. It consists of 43 career choices ranked by participants from strongly disagree to highly disagree on advice given to an adult male who stutters. Results: The study found that the participants were less likely to advise an adult male who stutters to pursue 42 of the 43 careers, when compared with advice given for an adult male who does not stutter. Participants reported that the lowest rated careers were judge, speech-language pathologists, and attorney. This finding supports the notion that PWS suffer from role entrapment, in that there appear to be limitations in the types of careers viewed to be appropriate and that careers rated lowest appear to be those that require high levels of communication. Conclusions: The findings suggest the presence of role entrapment in this group of students. Future research might consider using different research approaches, including qualitative studies, when studying role entrapment by HR students and professionals.